Ethenesulfonyl Fluoride: The Most Perfect Michael Acceptor Ever Found?. Issue 41 (9th May 2016) - Chen, Quan; Mayer, Peter; Mayr, Herbert
Abstract: The kinetics of the reactions of ethenesulfonyl fluoride (ESF) with sulfonium and pyridinium ylides were measured photometrically to determine the electrophilicity parameter of ESF according to the correlation lg  k 20 °C = s N ( N + E ). With E =−12.09, ESF is among the strongest Michael acceptors in our comprehensive electrophilicity scale, which explains its excellent performance in reactions with many nucleophiles. Its predicted usability as a reagent in electrophilic aromatic substitutions with electron‐rich arenes was confirmed by uncatalyzed reactions with alkyl‐substituted pyrroles. Abstract : Kinetic studies of the reactions of ethenesulfonyl fluoride and styrenesulfonyl fluoride with sulfonium and pyridinium ylides reveal that the SO2 F group activates C=C bonds 10 6 to 10 8 times more strongly towards nucleophilic attack than an SO2 Ph or SO2 Tol group. Ethenesulfonyl fluoride is thus one of the most electrophilic monosubstituted ethylenes ever reported (compare the electrophilicity parameters E ).